Work intensification and bullying among Ghanaian Nurses: Do psychological capital and life satisfaction matter? - Justice Mensah; Comfort Binipom Mpuan; Eric Nanteer-Oteng (International Journal of Africa Nursing Sciences)
The current study examined the effect of intensified job demands (IJDs) on workplace bullying among nurses in Ghana and explored the moderating role of psychological capital and life satisfaction. This study was a cross-sectional survey carried out with 406 nurses being sampled conveniently via the administration of an online survey. The results of the study showed that experiences of intensified job demands (IJDs) were associated positively with bullying behaviours among nurses. Furthermore, the results from Structural Equation Modeling (SEM) in IBM’s AMOS showed that life satisfaction and psychological capital (PsyCap) mitigated the extent to which nurses engaged in workplace bullying behaviours in the face of intensified job demands. Thus, the influence of IJDs on workplace bullying behaviours was significantly diminished in the presence of life satisfaction and PsyCap. It is therefore suggested that as organisations work towards the eradication of workplace bullying, they must pay attention to work intensification, develop the PsyCap of employees, and deploy measures that enhance the life satisfaction of employees.